FAMILY INVOLVEMENT IN EDUCATION OF SPECIAL NEEDS STUDENTS: A SYSTEMATIC LITERATURE REVIEW - Khairunnisa Mokhtar; Rozniza Zaharudin; Suzzanna Amir; Nurul Faizzah Mokhtar (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Family involvement is an essential element in the education concerning special needs students, and this systematic literature review is focused on investigating its significance and impact. It investigates the factors and elements that influence family involvement, its impact on student outcomes, and strategies for bolstering collaboration between families and educational institutions. While the importance of family involvement is widely recognized, challenges and knowledge gaps remain regarding its best practices and effects. The study utilized the PRISMA approach, conducting a systematic review by scouring academic databases and journals for pertinent articles published within the last five years. The systematic search employed academic databases like Scopus and Web Of Science. After rigorous searching, the final dataset comprised (n=24) studies. Three core themes emerged from this approach: Teacher-Parent Collaboration, Barriers and Challenges, and Effects on the Achievement of Students. The review underscores essential components of family involvement, including communication, collaboration, shared decision-making, and parent-teacher partnerships. It provides an in-depth exploration of how family engagement positively affects students’ academic and socio-emotional development while also shedding light on the obstacles and hindrances that can disrupt productive family-school collaborations. In conclusion, family involvement plays a pivotal role in the education of special needs students, significantly contributing to their holistic development. This review offers valuable insights for policymakers, educators, and researchers to further fortify family involvement in special education.